Hegemon as Idol. A Theoretical Proposal - Skórczewski, Dariusz (Porównania, 2016)
All populations need entertainment. This is true at each stage of their existence, even under most traumatic conditions. Therefore, description of experiencing foreign domination should take into account popular culture as the field of articulating both subalterns’ anticolonial resistance and their colonial subordination. The paper submits a proposal of exploring the latter, pointing to cultural mechanisms of the naturalization of the hegemon in subalterns’ discourse through hegemon’s idolization.